Design of segmental rotor and non-overlap windings in single-phase fefsm for low torque high speed applications - Omar, Mohd Fairoz (2020)
In this research, a new structure of single-phase field excitation flux switching motor (FEFSM) using segmental rotor structure and non-overlap windings arrangement is proposed in order to overcome the drawbacks of low torque and small power performances due to their longer flux path in the single-phase FEFSM using salient rotor structure and overlap windings arrangement. The objectives of this study are to design, analyse and examine performance of the proposed motor, to optimize the proposed motor for optimal performances, and to develop the proposed motor prototype for experimental performance validation. The design and analyses thru 2Dfinite element analysis (FEA) is conducted using JMAG Designer version 15, while deterministic optimization method is applied in design optimization process. To validate the 2D-FEA results, the motor prototype is developed and tested experimentally. Based on various rotor poles analysis, a combination of 12 pole 6 pole (12S-6P) has been selected as the best design due to their highest torque and power capability of 0.91 Nm and 277.4 W, respectively. Besides, the unbalance armature magnetic flux of the proposed FEFSM using segmental rotor has been resolved by using segmental rotor span refinement. The balanced armature magnetic flux amplitude ratio obtained is 1.002, almost 41.2% reduction from the initial design. In addition, the optimized motor has increased maximum torque and power by 80.25% to 1.65 Nm, and 43.6% to 398.6W, respectively. Moreover, copper loss of the optimized design has decreased by 9.7%%, hence increasing the motor efficiency of 25.3%. Finally, the measured results obtained from the prototype machine has reasonable agreement with FEA results, proving their prospect to be applied for industrial and home appliances.